Biocontrol Ability and Mechanism of a Broad-Spectrum Antifungal Strain Bacillus safensis sp. QN1NO-4 Against Strawberry Anthracnose Caused by Colletotrichum fragariae - Li, Xiaojuan; Zhang, Miaoyi; Qi, Dengfeng; Zhou, Dengbo; Qi, Chunlin; Li, Chunyu; Liu, Siwen; Xiang, Dandan; Zhang, Lu; Xie, Jianghui; Wang, Wei (Frontiers in Microbiology, 2021)
Strawberry is a very popular fruit with a special taste, color and nutritional value. Anthracnose caused by Colletotrichum fragariae severely limits fruit shelf life during postharvest storage. Use of traditional chemical fungicides leads to serious environment pollution and threatens food safety. Biocontrol is considered as a promising strategy to manage the postharvest fruit diseases. Here, strain QN1NO-4 isolated from noni (Morinda citrifolia L.) fruit exhibited a high antifungal activity against C. fragariae. Based on its physicochemical profiles and phylogenetic tree of 16S rRNA sequence, strain QN1NO-4 belonged to the genus Bacillus. Average nucleotide identity (ANI) calculated by comparing with two standard strain genomes was below 95-96%, suggesting that the strain might be a novel species of the genus Bacillus and named as Bacillus noliensis sp. QN1NO-4. Its extract effectively reduced incidence of strawberry anthracnose of harvested fruit. Fruit weight and TSS contents were also maintained significantly. The antifungal mechanism assays indicated that the extract of test antagonist inhibited mycelial growth and spore germination of C. fragariae in vitro. Cells of strain QN1NO-4 demonstrated the cytoplasmic heterogeneity, disappeared organelles and ruptured ultrastructure. Notably, the strain extract also had a broad-spectrum antifungal activity. Compared with the whole genome of strain QN1NO-4, several functional gene clusters involved in the biosynthesis of active secondary metabolites were observed. Fifteen compounds were identified by a gas chromatography-mass spectrometry (GC-MS). Hence, the fruit endophyte Bacillus noliensis sp. QN1NO-4 is a potential bio-agent identified for the management of postharvest disease of strawberry fruit.